O sistema sindical brasileiro e os impactos do reconhecimento das centrais sindicais como entidades sindicais - Polinesio, André Villac (2010)
The purpose of this paper is to analyze unions autonomy and freedom, especially the existing and established paradoxes in the Brazilian union laws, specifically those arising from Law nr. 11.648/08, including legal, political and structural issues. The laws and legal teachings that govern this matter were analyzed, with special emphasis on the dualities and conflicts of the Brazilian system, further to situational movements that directly or indirectly affect this matter. Moreover, we shall analyze the impacts arising from the attempted recognition of Union Center as union entities, as provided in Law nr. 11.648/08, as well as the direct impacts, including those relative to the constitutionality of such legal provision, since, in our understanding, it disregards the union unicity principle, provided in article 8 of the Federal Constitution of 1988. The conclusion is that a full Rule of Law system within a democratic geographic space is only possible upon the existence of free and independent unions that may enjoy the guarantee of representing the group to which they support and so that the persons may legitimately and legally assure and enforce such groups rights. As a result, the unions freedom and autonomy become increasingly important, reflecting Convention nr. 87, of the International Labor Organization, in light of its practical applicability for the Brazilian union system. However, in our opinion, the intended fact, via imposition of ordinary law, finds an unsurmountable constitutional obstacle, and for this reason - even due to the fact of it being a necessary change - the unconstitutionality of such legislation should be acknowledged further to the immutability of such confederate union s structure